Wacana Pemakzulan Gibran Rakabuming Raka: Mekanisme, Proses, dan Dampaknya - Arkan, Muhammad Hanif; Putri, Angelica Anastasia; Ramdhani, Muhammad Syahrul; Salma, Athifa Huurun; Maharani, Nabilah Liztha; Khairunnisa, Nasywa; Dalida, Naumy Syauqina; Sihombing, Suluganwata (Media Hukum Indonesia (MHI), 2025)
The impeachment discourse against Gibran Rakabuming Raka as Vice President of Indonesia after the 2024 General Election has sparked national legal and political controversy. This arti le aims to comprehensively examine the impeachment mechanism according to the 1945 Constitution, the political process dynamics involved, and its impact on the stability of Indonesian democracy. The method applied is a systematic literature review of Indonesian-language scholarly journals and national media publications from 2023 to 2025. The findings indicate that although the impeachment procedure is strictly regulated through the House of Representatives, Constitutional Court, and People’s Consultative Assembly, the current discourse is predominantly driven by ethical sentiment and public distrust toward the neutrality of state institutions, particularly the Constitutional Court. The lack of sufficient legal evidence shows that the impeachment narrative is largely symbolic and political in nature, which in turn may provoke public polarization and diminish the quality of constitutional democracy. This review recommends strengthening constitutional literacy, upholding the rule of law, and reforming institutions to prevent the misuse of legal discourse in elite political conflicts